Excel-VBA : from solving mathematical puzzles to analysing complex engineering problems - Muneer, T.; Ivanova, Stoyanka (Springer, 2022)
This compact text is a powerful introduction to the Excel/VBA computing environment. The book presents some of the most useful features of Excel. First by introducing mathematical puzzles that will grab the readers attention with the reader invited to think hard on solving those puzzles. Then, solutions are presented in a logical manner. The book goes on to describe modern and up-to-date engineering problems and their solutions. Based on many years of the authors teaching, the book provides a practical, useful and enjoyable learning methods for readers to become expert in Excel and its application to engineering.
Keywords: Microsoft Excel (Computer file); Electronic spreadsheets.; elektronické knihy; electronic books